MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS SISWA DALAM MENGHADAPI ERA REVOLUSI 4.0: IMPROVING STUDENTS' ENGLISH SPEAKING SKILLS IN FACING THE ERA OF REVOLUTION 4.0 - Siagian, Rusliani Octavia; Handayani, Tuti; Amdhannur, Suryadi; Ihsan, Muhammad Taufik (Education and Talent Development Center of Indonesia (ETDC Indonesia)., 2023)
Many individuals expect that learning languages are not difficult since they think we need to utilize language consistently. Learning a language is not simply to speak with the language, but also to know and comprehend the importance contained in the words or expressions verbally expressed. In learning languages, particularly English, most people experience challenges in talking abilities. The trouble is normally about the challenges in communicating thoughts verbally, limited vocabulary, limited grammar ability it is hard to talk with the right guidelines, limited ability capacity to articulate words (pronunciation) accurately. This outcome in the students' troubles to articulate the words accurately and lack of courage to talk since they fear committing errors. There are a few compelling ways of further developing students' talking abilities, namely improving vocabulary, reading aloud, recognizing English grammar, reading English writing, practicing English discussion, paying attention to English songs, watching English movies, and being enamored with English. This paper additionally talks about the strategy for showing utilizing pretend and media of teaching using role-play and picture strip stories to further develop students' English talking abilities.